Two new species of Connarus (Connaraceae) from Brazilian Atlantic Forest - Toledo, Cássio A.p.; Souza, Vinicius Castro; Lucas, Eve J. (Phytotaxa, 2019)
Two new species of Connarus are here described and illustrated: C. aureus and C. tomentosus. These taxa are until now known only to the Atlantic Forest in Southeastern Brazil. Diagnostic characteristics of the new species and an identification key of Connarus from Bahia and Espírito Santo states are provided, along with information on their habitat and ecology.